Legal Responsibility Of Regional Grant Recipients For The Utilization Of Regional Budget (APBD) Funds In Ensuring Public Financial Accountability - Putu Agus Suwantara; Erham; Iksan (Lembaga Bale Literasi, 2025)
Regional grants constitute one of the fiscal policy instruments intended to support the implementation of governmental functions that are closely associated with regional interests. One practical manifestation of this policy is the provision of regional grants by the Government of Bima City to the Bima City Regional Police (Polres Bima Kota) to strengthen the implementation of public security and law enforcement functions. The primary issues addressed in this study concern the legal responsibility of regional grant recipients in utilizing funds originating from the Regional Revenue and Expenditure Budget (APBD) and the supervisory mechanisms that ensure accountability in the use of such grants. This research aims to analyze the legal responsibilities of regional grant recipients and to examine the effectiveness of oversight mechanisms governing the utilization of grant funds by the Bima City Regional Police. The study employs normative legal research using statutory, conceptual, philosophical, and case approaches. Legal materials were analyzed through descriptive qualitative methods based on library research encompassing legislation, legal doctrines, and official documents concerning regional grant management. The findings indicate that the legal responsibility of grant recipients extends beyond administrative accountability through financial reporting to include civil, administrative, and criminal liability whenever misuse of grant funds results in state financial losses or violations of applicable laws. Furthermore, the supervision of regional grants is conducted through both internal and external oversight mechanisms; however, its effectiveness remains influenced by inter-institutional coordination, compliance with legal provisions, and the administrative capacity of grant recipients. This study proposes strengthening an accountability-based grant supervision model as an effort to promote transparent, effective, and legally compliant regional financial governance while enhancing public accountability in the management of regional grants.